Estrat??gia em terceiriza????o de servi??os log??sticos resiliente, sob a ??tica da vis??o baseada em recursos. - Oliveira Neto, Geraldo Cardoso de (2013)
In most cases, organizational executives consider the logistics sector and the supply network as a support activity, and when they decide to outsource these services aim to reduce operating costs and to redirect the responsibilities for logistics operator. However, the logistics sector and the supply network is responsible for availability of products at the right time and under the conditions desired by customers, so if any disruption, this may decrease the performance of the organization in the market, thereby forcing the target the need to develop strategy. This thesis aims to develop the strategic aspects and evolution of strategy in the context of outsourcing of logistics services, in order to design models and test them in Brazilian companies. In particular, it aims to (i) propose a strategic model for outsourcing of logistics services, based on the literature and field research. The literature review was based on the Theory of Resource-Based View, Risk and Resilience, Transaction Cost Theory, Theory of Contingency and Institutional Theory, (ii)propose a model and questions based on the Theory of Resource-Based View that orient the manager of the supply chain to develop strategy for outsourcing of logistics services, starting from the operational structure, establishing the necessary resources, capabilities and core operating routines, and (iii) assess the degree of importance attributed by managers of chain supplies and logistics companies carrying flammable liquids fractionated to the attributes of the formulation, implementation and control of strategy model for outsourcing of logistics services based on the Resource Based View Theory. The results and conclusions indicate five main strategic activities of outsourcing of logistics services: (1) identification of resources, (2) mapping of logistical routines, (3) development of skills and knowledge in a cooperative manner, (4) completion of logistical capacity of company, and (5) risk management and resilience. These strategic issues are endogenous to the unfolding of the strategy for outsourcing of logistics services. Threefold strategy were developed in outsourcing of logistics services, through descriptive theoretical research, to be applied in eleven steps, quote: (i) formulation: Blame the manager of the supply chain in relation to decision making to manage, resources, risk and resilience in the OPL contractor and (ii) implementation: ability to select OPLs to establish hierarchy, based on criteria in the analysis of operational strategic similarity, to provide coordination and collaboration and contractual formalization of contracts by sector, and (iii) control: capacity management performance to allocate the supervisor of the contractor in the outsourced operation, deployment of an integrated system to perform performance tracking, require periodic performance reports and daily meetings to continuous improvements and contract renegotiations. In this study, seven propositions to be surveyed were identified. Of this total, the first three hypotheses guided the research to test the model by means of Structural Equation Modeling. The strategy formulation showed a strong relationship with the control strategy (0.915), demonstrating the strategic importance of identifying critical tasks in routine contractor for implementation of performance indicators with rewards and punishments. The control strategy showed substantially stronger relationship with the implementation phase (0.614), mainly because it is necessary to manage the performance of the implementation to mitigate risks in the integration between companies. However, there was a moderate relationship between the formulation and implementation of strategy (0.333), indicating a need for more time to strengthen the formulation.